Bilateral Insufficiency Fractures of Hip with SIF A Case Report and Literature Review (Journal of Pakistan Orthopaedic Association, 2018)
Multiple Insufficiency fracture is a rare injury. To have a compression Sub Chondral Insufficiency fracture (SIF) in same hip is even rarer. The author's report an elderly lady with osteoporosis who had stress fractures of her spine with subsequent insufficiency fractures of both hips and a SIF. The patient's pain was eventually resolved with sequential total hip replacements. We believe that this is an unusual presentation of a rare injury and has never been reported before. We describe the circumstances and a literature review